A comparative study on the bead profile and microstructural characteristics of aluminum alloy welds produced by single and double pulsed tandem gas metal arc welding. (21st June 2019) - Wu, Kaiyuan; Liu, Zhao; Xie, Peimin; Zeng, Min; Wang, Jiajia
Abstract: In this study, both single-pulsed (SP) and double-pulsed (DP) tandem gas metal arc welding (GMAW) were conducted on aluminum (Al) alloy, and the methods were compared in relation to the effects of SP and DP tandem GMAW on the bead profile and microstructural characteristics of the resulting Al alloy welds. The results show that DP tandem GMAW is more stable and produces a more ideal bead profile with prominent fish-scale ripples in the weld bead and less spatter. In addition, the penetration was deeper and weld beads exhibited waviness along the longitudinal direction. The results demonstrate the advantage of the stirring effect produced by DP tandem GMAW, which promotes the escape of pores to the upper section of the weld bead, and creates more refined weld grains compared to SP tandem GMAW.